THE IMPLEMENTATION OF FREE LEGAL AID (PRO BONO) AS ACCESS TO JUSTICE IN CRIMINAL CASES IS REVIEWED BASED ON LAW NUMBER 16 YEAR 2011 ON LEGAL AID (Study at LBH Solo Raya Office) - Andi Muhammad Santoso; Supriyanta Supriyanta; Esti Aryani (Wacana Hukum, 2021)
Indonesia is a country based on law (rechtsstaat), and is not based on mere power (machtsstaat) where guaranteeing respect for the right to justice and equality before the law is an obligation of the state. However, in practice, access to justice and equality in the face of the law is not evenly distributed to all groups, especially for the poor or poor. Often, when dealing with the law, the rights of suspects / defenders are not able to be fulfilled properly, especially the right to obtain free legal assistance (pro bono). Based on this, Law No. 16 of 2011 on Legal Aid was born to guarantee the exercise of the right to legal aid and is arranged in an orderly order so that it is expected to realize justice and equality of standing before the law for the poor.